2009
DOI: 10.1007/s11802-009-0296-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of stocking density for the sea cucumber, Apostichopus japonicus Selenka, under feed-supplement and non-feed-supplement regimes in pond culture

Abstract: Optimal stocking densities were investigated for the sea cucumber Apostichopus japonicus Selenka under feed-supplement and non-feed-supplement regimes in net enclosures for 333 d. Substantial weight loss occurred during the aestivation phase (AE). Decreased growth rates were also observed during the winter phase (WT). In contrast, sea cucumbers showed rapid growth during the spring (SP) and autumn (AU) phases. Feeding regimes considerably influenced the growth performance, i.e., sea cucumbers grew faster under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…Highly variable SR ranges were obtained in early H. scabra juveniles depending on juvenile size (52–100%) and density (5.9–15.7%) being greater in larger individuals and at lower densities (Battaglene et al, ). These results indicate that, for I. badionotus juveniles, survival could be affected by size but also evidence that size does not have as drastic an effect as that reported for other species, even after culture system and densities were changed, which can also be attributed to the fact that the natural food sources used in this study were good enough for these early juvenile stages and that the initial and final densities over trial periods were below the range that could become limiting (Battaglene, ; Qin et al, ; Ramofafia, ).…”
Section: Discussionsupporting
confidence: 63%
“…Highly variable SR ranges were obtained in early H. scabra juveniles depending on juvenile size (52–100%) and density (5.9–15.7%) being greater in larger individuals and at lower densities (Battaglene et al, ). These results indicate that, for I. badionotus juveniles, survival could be affected by size but also evidence that size does not have as drastic an effect as that reported for other species, even after culture system and densities were changed, which can also be attributed to the fact that the natural food sources used in this study were good enough for these early juvenile stages and that the initial and final densities over trial periods were below the range that could become limiting (Battaglene, ; Qin et al, ; Ramofafia, ).…”
Section: Discussionsupporting
confidence: 63%
“…During industrialized stocking, SGR, DCV, DSD and SR are important indicators that affect the yields of A. japonicus. Qin et al (2009) analysed and described the relationships among weight, density and yield of A. japonicus using B-N and M-N models and determined the best stocking density for A. japonicus in pond culture. However, the effects of density and growth traits are interactive and their effect on yield changes over time.…”
Section: Integral Regression Relationship Between Key Growth Traits Amentioning
confidence: 99%
“…In high‐density regimes, sea cucumbers become food limited, which in turn affects growth (Slater & Carton ). Qin, Dong, Tan, Tian, Wang, Dong and Gao () argued that density rarely affected the survival of sea cucumber, but that increases in density are negatively correlated with growth rate. Liang, Dong, Gao, Wang and Tian () and Pei, Dong, Wang, Tian and Gao () compared variation in growth between A. japonicus that were reared in groups or alone.…”
Section: Introductionmentioning
confidence: 99%
“…The sea cucumber Apostichopus japonicus (Selenka) is one of the most commercially important mariculture species in northern China in recent years (Chen, 2004;Dong et al, 2007;Qin et al, 2009). However, it is found that individual growth variation of this species is exceptionally great in both nature and culture practice.…”
Section: Introductionmentioning
confidence: 99%